Non-synonymous polymorphism in IGFBP-3 gene associated with growth traits in striped catfish (Pangasianodon hypophthalmus, Sauvage, 1878) - Tran, Trang Thi Huyen; Le, Binh Thi Nguyen; Nguyen, Sang Van; Kim, Oanh Thi Phuong (Vietnam Journal of Biotechnology, 2023)
Insulin-like growth factor binding protein-3 (IGFBP-3) has an important role on the growth of teleost fish. The association between genetic variations of IGFBP-3 gene and the growth of striped catfish, Pangasianodon hypophthalmus, was investigated in this study. To discover SNPs, fragments of IGFBP-3 gene from 10 fast-growing fish and 10 slow-growing fish were directly sequenced. Among 10 putative SNPs, a non-synonymous SNP 704 C>G (p.Leu8Val) located at coding region of exon 1 was filtered and subjected to validate in 70 fast-growing fish and 70 slow–growing fish by individual genotyping. Our statistical analysis showed the significant association between SNP 704 C>G (p.Leu8Val) and growth traits of striped catfish (p < 0.01). The genetic diversity of the SNP was evaluated by polymorphism content (PIC) and minor allele frequency (MAF). These values indicated that this SNP was common variant with moderate genetic diversity. The non-synonymous SNP 704 C>G (p.Leu8Val) in IGFBP-3 gene is a potential candidate for subsequent development of molecular marker for growth traits in breeding of the striped catfish.